2015
DOI: 10.1021/acs.energyfuels.5b00048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mixed Fe–Mn Oxide System for Chemical Looping Combustion

Abstract: In coal-based chemical looping combustion (CLC) technology, relatively cheap metal oxides, referred to as oxygen carrier materials (OCMs), are required because some of the OCMs will be removed together with the residual ashes after combustion. CLC technology will have an estimated loss in efficiency of around 2% compared to standard combustion technology without capture if a proper OCM is found that can give full combustion, removing the need of an air separation unit (ASU). Materials with a chemical looping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…This is in agreement with the Lambert et al [53], who observed that bixbyite regeneration reaction kinetics was always very slow for Mnrich solids. Consequently, Larring et al [54] postulated that in order to take advantage of the oxygen release capability of these materials, an exhaustive control of oxidation conditions, i.e., temperature and partial pressure of oxygen, is essential. Taking this into account, Pérez-Vega et al [55] delimited operating temperature range for the CLOU process of a Mn-rich oxygen carrier selected after a screening process.…”
Section: State Of Development Of Manganese-iron Mixed Oxides As Oxygementioning
confidence: 99%
“…This is in agreement with the Lambert et al [53], who observed that bixbyite regeneration reaction kinetics was always very slow for Mnrich solids. Consequently, Larring et al [54] postulated that in order to take advantage of the oxygen release capability of these materials, an exhaustive control of oxidation conditions, i.e., temperature and partial pressure of oxygen, is essential. Taking this into account, Pérez-Vega et al [55] delimited operating temperature range for the CLOU process of a Mn-rich oxygen carrier selected after a screening process.…”
Section: State Of Development Of Manganese-iron Mixed Oxides As Oxygementioning
confidence: 99%
“…Recently the mixed oxides have been synthesized and tested mostly using gaseous fuels. As Mn content in the oxide increases up to 33% the oxygen uncoupling increase to 2% between 800 and 1100 °C [91]. To optimize the cost of the oxygen carrier in the CLOU process, a long life and/or a low cost of oxygen carrier are considered and still a challenge [92].…”
Section: Challenges and Recent Research On The Clou Processmentioning
confidence: 99%
“…expensive nickel oxide to low-costing ores, [6][7][8] several hundreds of materials based on Ni, Cu, Fe, Mn, Co,and mixtures of these materials have been studied as potential OCMs for CLC. [9] Lately,t here has been significant interest in mixed transition-metal oxides [10] and complex perovskite-type oxides, [11] especially those derived from the calcium manganite CaMnO 3Àd family.F or CLC applications, substitution of calcium by strontium and barium [12] has been considered. Furthermore,t he substitution of manganeseb ym agnesium, [13] titanium, [4,14] or ac ombinationo fb oth [15] has been investigated.…”
Section: Introductionmentioning
confidence: 99%